3D Printing Technology in Design of Pharmaceutical Products - Ameeduzzafar; Alruwaili, Nabil K.; Rizwanullah, Md.; Abbas Bukhari, Syed N.; Amir, Mohd; Ahmed, Muhammad Masood; Fazil, Mohammad (Current Pharmaceutical Design, 2018)
Background: Three-dimensional printing (3DP) is a novel technology for fabrication of personalized medicine. As of late, FDA affirmed 3D printed tranquilize item in August 2015, which is characteristic of another section of Pharmaceutical assembling. 3DP incorporates a wide range of assembling procedures, which are altogether founded on computer-aided design (CAD), and controlled deposition of materials (layer-by-layer) to make freestyle geometries. Conventionally, many pharmaceutical processes like compressed tablet have been used from many years for the development of tablet with established regulatory pathways. But this simple process is outdated in terms of process competence and manufacturing flexibility (design space). 3DP is a new technology for the creation of plan, proving to be superior for complex products, customized items and items made on-request. It creates new opportunities for improving efficacy, safety, and convenience of medicines. Method: There are many of the 3D printing technology used for the development of personalized medicine on demand for better treatment like 3D powder direct printing technology, fused-filament 3D printing, 3D extrusion printer, piezoelectric inkjet printer, fused deposition 3D printing, 3D printer, ink-jet printer, micro-drop inkjet 3DP, thermal inkjet printer, multi-nozzle 3D printer, stereolithographic 3D printer. Result: This review highlights features how item and process comprehension can encourage the improvement of a control technique for various 3D printing strategies. Conclusion: It is concluded that the 3D printing technology is a novel potential for manufacturing of personalized dose medicines, due to better patient compliance which can be prepared when needed.
Keywords: personalized medicine